Alcohol-clozapine synergism triggering rhabdomyolysis at subtoxic levels: a case report and literature review - Zhou, Wenzhen; Sun, Yuxin; Dai, Mingcheng; Ma, Senlin; Lu, Qiuxin; Qian, Junwei; Shang, Zhaoming; Zhou, Kangshuai; Chen, Mingquan; Jiang, Xiaofei (Frontiers in Toxicology, 2025)
BackgroundWhile excessive oral intake of clozapine is known to cause severe complications, this case report highlights that even conventional doses of clozapine ingested after alcohol consumption–without reaching toxic concentrations–can lead to the rare complication of rhabdomyolysis when synergistic effects occur between the two substances.Case presentationWe report a case of a 39-year-old male patient who presented with impaired consciousness 1 day after consuming 500 g liquor followed by ingestion of 8 clozapine tablets (200 mg total). Toxicology screening upon admission indicated subtoxic levels of clozapine. Laboratory findings confirmed rhabdomyolysis, acute kidney injury, and myocardial damage. During hospitalization, the patient underwent hemopurification and fluid resuscitation. His consciousness improved significantly, accompanied by marked improvement in creatine kinase (CK) levels, renal function, and cardiac enzymes. At 15-day follow-up, renal function, CK levels, and cardiac enzymes had returned to within normal limits.ConclusionIn patients consuming clozapine after alcohol intake, dynamic monitoring of CK and myoglobin should be implemented regardless of whether toxicology results are within normal limits. Early implementation of blood purification can effectively disrupt the rhabdomyolysis-renal injury cascade, thereby securing a critical therapeutic window for clinical intervention.